Anxiety and Leisure-Domain Physical Activity Frequency, Duration, and Intensity During Covid-19 Pandemic - Meira, Cassio M.; Meneguelli, Kaique S.; Leopoldo, Maysa P. G.; Florindo, Alex A. (Frontiers in Psychology, 2020)
This study investigated relationships between state anxiety and leisure-domain physical activity levels during Covid-19 pandemic. We used frequency, duration, and intensity as key variables of physical activity. Trait anxiety, state anxiety before pandemic, age, gender, and education level were also included in the analysis. Our general hypothesis was that participants who declared doing more physical activity levels would exhibit lower levels of anxiety during the Covid-19 pandemic. A convenient sample of 571 volunteer adults (mean age 39 ± 14 years) was drawn mainly from Sao Paulo State (89.2% of the sample), the epicenter of Covid-19 pandemic in Brazil. To obtain the participants’ levels of anxiety (trait, state before pandemic, and state during pandemic) we used a validated short-version of the State and Trait Anxiety Inventory. Levels of physical activity were measured via questions from VIGITEL, a validated questionnaire about the individual’s habits on risk factors. Answers were given regarding the first week of March 2020 (before pandemic) and at the very moment the participant was filling in the electronic form (June 2020). Data analyses were conducted through descriptive and inferential techniques, with the use of non-parametric tests and linear regression models. Overall, participants’ responses indicate that anxiety levels were higher during the pandemic compared to the period that preceded the pandemic, and that frequent and long physical activity in the leisure-domain reduced anxiety, regardless its intensity. The regression models revealed an inverse relationship between physical activity and anxiety (the more physical activity, the less anxiety) and independent of gender, age, education level, trait anxiety, and physical activity before pandemic.